Influence of Positioning Strategy and Relationship Marketing towards Brand Imaging and Their Implication towards Brand Loyalty - Ismail, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
Objective of the study is to investigate simultaneous and partial effect of Positioning and Relationship Marketing Strategies, as perceived by customers, towards Brand Image on customers of pre-paid GSM providers in Makassar. The population was all customers of pre-paid GSM cellular providers in Makassar. The sampling technique was stratified random sampling. The sample was categorized based on GSM cellular provider (brand) they used. First, Positioning strategy and Relationship marketing have positive, partial and simultaneous influence towards Brand Image of the pre-paid GSM cellular provider customers in Makassar. Secondly, Positioning Strategy Relationship Marketing and Brand Image have simultaneous influence towards Brand loyalty of the pre-paid GSM cellular provider customers in Makassar. Partially, Brand Image has stronger influence towards Brand Loyalty. Therefore, substantially, brand loyalty depends on brand image as the content factor while positioning strategy and relationship marketing become the contextual factors. The originality of this study is that this is a comprehensive study analyzing relationship between Performance of Positioning and Marketing Strategy, Their Relationship to Brand Image and Its Implications towards Brand Loyalty.